2014
DOI: 10.3389/fnhum.2014.00549
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy (NIRS) as a new tool for neuroeconomic research

Abstract: Over the last decade, the application of neuroscience to economic research has gained in importance and the number of neuroeconomic studies has grown extensively. The most common method for these investigations is fMRI. However, fMRI has limitations (particularly concerning situational factors) that should be countered with other methods. This review elaborates on the use of functional Near-Infrared Spectroscopy (fNIRS) as a new and promising tool for investigating economic decision making both in field experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 101 publications
1
83
0
2
Order By: Relevance
“…Therefore, research methods in this area are currently reliant on behavioral tasks suitable for an fMRI environment, which compromises ecological validity. In future research, methods should be developed to transfer these findings to real life and to organizational situations-functional near-infrared spectroscopy, for example (see Kopton & Kenning, 2014). Furthermore, the use of a strict follow-up order of our experimental design was necessary for our given research question but might have produced different results than a different order or a more randomly chosen order.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, research methods in this area are currently reliant on behavioral tasks suitable for an fMRI environment, which compromises ecological validity. In future research, methods should be developed to transfer these findings to real life and to organizational situations-functional near-infrared spectroscopy, for example (see Kopton & Kenning, 2014). Furthermore, the use of a strict follow-up order of our experimental design was necessary for our given research question but might have produced different results than a different order or a more randomly chosen order.…”
Section: Discussionmentioning
confidence: 96%
“…These neural changes are expected to be paralleled by changes in performance in the experiment. Previous research shows that increasing the reward received from a desired outcome can facilitate cognitive processes that are required for the achievement of that outcome (Adcock, Thangavel, Whitfield-Gabrieli, Knutson, & Gabrieli, 2006;Delgado, Gillis, & Phelps, 2008;Engelmann, Damaraju, Padmala, & Pessoa, 2009;Jimura, Locke, & Braver, 2010;Kouneiher, Charron, & Koechlin, 2009;Krawczyk, Gazzaley, & D'Esposito, 2007;Taylor et al, 2004). Thus, we assume that when performance-based rewards are introduced, activation in task-related areas such as the IPL will increase, reflecting the increased effort and cognitive engagement.…”
Section: Neural Correlates Of Changes In Performance-based Rewardsmentioning
confidence: 98%
“…agriculture [1], Chinese medicine [2], [3], neuro-economic research [4], and food industry [5] to potentially replace conventional measurement approaches (e.g. sensory evaluation and chemical analysis) that are timeconsuming, expensive per measurement, destructive, or inconvenient.…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicate that the cross-validation approach is a good approach to estimate the final model without over-fitting, and the proposed shortwave NIR spectroscopy was able to estimate the peak value of the acquired spectrum from NIR LEDs with RMSE of 1.1616nm. [4], and food industry [5] to potentially replace conventional measurement approaches (e.g. sensory evaluation and chemical analysis) that are timeconsuming, expensive per measurement, destructive, or inconvenient.…”
mentioning
confidence: 99%
“…Measurement of cerebral blood flow (CBF) related to texture also involves the influence of body movements. On the other hand, Kopton and Kenning [6] suggested that further research using mobile fNIRS could be a valuable tool in developing the potential of new field experiment methodologies.…”
Section: Introductionmentioning
confidence: 99%